THE INFLUENCE OF PRODUCT REVIEW AND SOURCE CREDIBILITY BY BEAUTY VLOGGER ON CONSUMER BUYING DECISIONS OF LOCAL COSMETIC PRODUCTS IN MANADO - Palilingan, Lingkan N.; Pangemanan, Sifrid S.; Wangke, Shinta J. C. (Universitas Sam Ratulangi, 2021)
At this era, make-up and personal care are increasingly becoming integral part of Indonesian lifestyles, especially for a woman. Indonesian local cosmetic company is growing with the advantages of colors and materials that suitable with Indonesian women’s skin. Some things that cause consumers to buy a local cosmetic product are based on product review and source credibility of social influencer / beauty vlogger. This study is to know the influence of product review and source credibility by beauty vlogger on consumer buying decisions of local cosmetic products in Manado. The type of this research is quantitative research method and the population is the people in Manado who have experience using local cosmetic product The sampling technique in this study used convenience sampling method. Based on data result concluded that: product review has significant effect on consumer buying decisions and source credibility has significant effect on consumer buying decisions in Manado. If the Product Review from Beauty Vlogger’s viewers video is higher, then the consumer buying decision will increase. Keywords: consumer buying decisions, product review and source credibility